THE IMPACT OF INCREASED GOVERNMENT SPENDING AND EXPENDITURES AND EXPORTS OF MAIN COMMODITIES ON DIY'S GRDP IN THE TIME OF COVID-19 - Freddy Wangke (Media Ekonomi, 2021)
To analyze the increase in government spending and expenditure as well as exports of Special Region of Yogyakarta (DIY)'s mainstay commodities by 10% each to DIY's GRDP in a historical forecasting simulation and to analyze this increase against other variables in the model other than DIY's GRDP. The model of government spending and expenditure as well as the export of the mainstay commodity of DIY is formed by the form of a simultaneous equation system. The system describes the behavioral and identity equations of all endogenous and exogenous variables in the hope of producing parameter estimators that are theoretically and empirically appropriate. The developed model is dynamic by entering the endogenous Lag (L) variables into the behavioral equation. The increase in government spending and expenditure and an increase in DIY exports by 10% each can increase DIY's GDP by 9,608 IDR (million IDR) or a change of 0.60%. This increase led to an increase in regional and foreign investment by 72,042 IDR (million IDR) or 8.96%, employment of 16027 people or 1.11%, an increase in the value of technology 7,662 IDR (million IDR) or 5.23%, and the number of businesses 21 units or 0.55%.